The Emerging Role of Interdisciplinarity in Clinical Psychoanalysis - Steinmair, Dagmar; Löffler-Stastka, Henriette (Frontiers in Psychology, 2021)
Abstract Given the tight interconnections proposed between brain and psyche, psychoanalysis was conceptualized as an interdisciplinary theory right from the beginning. The diversification of knowledge performed by different science and technology fields, concerned with the same matter (explaining mind and brain and connecting them), makes this interdisciplinarity even more visible and evident. This challenges the integrative potential lying in psychoanalytic meta-theory.